2013
DOI: 10.21668/health.risk/2013.1.09.eng
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and hygienic safety assessment of the aqueous suspension of nano-dispersed silicon dioxide, synthesized using liquid-crystal templating

Abstract: Abstract.Experimental research has shown that after intragastric administration of a water suspension of nanodispersed silicon dioxide particles synthesized by the method of templating the tested product falls in hazard class 3 by criteria LD50. A number of morphological changes were detected in the least researched dose of 500 mg/kg, in particular, gross changes in the blood circulatory system in the form of vascular distention, kidney, liver, and thymus. Other changes included lymphoid and macrophage prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, the performance of the immune system in this study has not been investigated. It can be assumed that the main reason for the discrepancy in results [6,7] and [3,4], was the difference in the properties of the SiO 2 preparations used. It should be noted that all types of nanostructured SiO 2 studied in [2][3][4][5][6][7] are not used in consumer goods, including food.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the performance of the immune system in this study has not been investigated. It can be assumed that the main reason for the discrepancy in results [6,7] and [3,4], was the difference in the properties of the SiO 2 preparations used. It should be noted that all types of nanostructured SiO 2 studied in [2][3][4][5][6][7] are not used in consumer goods, including food.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that the main reason for the discrepancy in results [6,7] and [3,4], was the difference in the properties of the SiO 2 preparations used. It should be noted that all types of nanostructured SiO 2 studied in [2][3][4][5][6][7] are not used in consumer goods, including food. The study of subacute oral toxicity of NPs with a primary particle size of 5-30 nm showed the absence of noticeable signs of toxic effects when NM was administered for three months at a dose of up to 100 mg/kg bw daily by integral indicators, including weight gain, and permeability of the intestinal barrier to macromolecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations